2018
DOI: 10.18480/jjae.20.0_18
|View full text |Cite
|
Sign up to set email alerts
|

What Leads Farmers to Abandon Coffee Production?: An Experimental Study on Crop Choice in Chumphon Province, Thailand

Abstract: Our study examines farmers' crop choice to investigate the motivation behind the recent coffee production decrease in Chumphon, a southern province of Thailand. Through a choice experiment based on a random parameter logit model, which takes into account farmers' heterogeneous preferences for commodities, we find that the constraint on hiring labor induces farmers to refrain from replanting new coffee trees. In addition, the coffee tree aging problem induces the removal of old coffee trees, but does not affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This, combined with the fact that the farmers had to walk 10 minutes to their land and used only organic fertilizers that were likely generated exclusively on the farm, indicates that they were resource-constrained and interested in a quick return on their labor. The establishment and production of perennial crops such as coffee and banana is labor intensive, with coffee also needing pricey agricultural inputs such as pesticides and synthetic fertilizers (Clay et al, 2016;Kwanmuang & Lertjunthuk, 2021;Ngeleza et al, 2011). Previous studies found that biotic constraints (coffee twig borer) and poor management practices (unproductive coffee trees and low coffee plant density) restrict coffee production in central Uganda (Kiyingi and Gwali, 2012;Sseremba et al 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This, combined with the fact that the farmers had to walk 10 minutes to their land and used only organic fertilizers that were likely generated exclusively on the farm, indicates that they were resource-constrained and interested in a quick return on their labor. The establishment and production of perennial crops such as coffee and banana is labor intensive, with coffee also needing pricey agricultural inputs such as pesticides and synthetic fertilizers (Clay et al, 2016;Kwanmuang & Lertjunthuk, 2021;Ngeleza et al, 2011). Previous studies found that biotic constraints (coffee twig borer) and poor management practices (unproductive coffee trees and low coffee plant density) restrict coffee production in central Uganda (Kiyingi and Gwali, 2012;Sseremba et al 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Agricultural factors targeted the size of land dedicated to banana and coffee growing and crop yields (Apanovich & Mazur, 2018), as well as fertilizer use (organic vs. inorganic), pest management, and soil management (Pender et al, 2004, Mukuve & Fenner, 2015Karamage et al, 2017). The use of synthetic inputs serves as a proxy for capital, because only those with access to cash can purchase inputs (Kwanmuang & Lertjunthuk, 2021;Silva et al, 2019). We hypothesized that crop management would be signi cant in establishing farm typologies.…”
Section: Description Of Explanatory Variablesmentioning
confidence: 99%
“…Buyers of palm, durian, and coconut basically provide the harvest labor for farmers. For coffee, the harvest depends highly on the seasonal immigrant labor from the northeastern part of the country (Suksavead et al 2012;Napaporn 2014;Kwanmuang et al 2018)…”
Section: Chumphon and Its Crop Profilesmentioning
confidence: 99%
“…At the plot and / or farm levels, the mixing of some commodities is common. The study area survey shows the mixed crop, or intercrop, between coffee, durian, palm, and rubber(Kwanmuang et al 2018).In this section, the transition in crop diversification at the farm household level is discussed based on the survey data from regions where coffee production was previously active. There has been a drastic increase in the diversification of crop choice.…”
mentioning
confidence: 99%
See 1 more Smart Citation